2008
DOI: 10.1007/s10772-009-9041-9
|View full text |Cite
|
Sign up to set email alerts
|

Sense abstractness, semantic activation, and word sense disambiguation

Abstract: Concrete concepts are often easier to understand than abstract concepts. The notion of abstractness is thus closely tied to the organisation of our semantic memory, and more specifically our internal lexicon, which underlies our word sense disambiguation (WSD) mechanisms. Stateof-the-art automatic WSD systems often draw on a variety of contextual cues and assign word senses by an optimal combination of statistical classifiers. The validity of various lexico-semantic resources as models of our internal lexicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A first evaluation of the annotation is based on internal coherence. We recorded the average abstractness of the values along all dimensions: also based on literature (see, e.g., [10,7]) we expect that concrete vectors are, on average, more connected to other concrete concepts (e.g., through the Synonym relation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A first evaluation of the annotation is based on internal coherence. We recorded the average abstractness of the values along all dimensions: also based on literature (see, e.g., [10,7]) we expect that concrete vectors are, on average, more connected to other concrete concepts (e.g., through the Synonym relation).…”
Section: Discussionmentioning
confidence: 99%
“…The role of abstractness has also been explored in the context of the Word Sense Disambiguation [10], leading to the finding that words with very high or very low score of abstractness are easier to disambiguate. Along this line, the association of word senses with senses of di↵erent words have been examined, finding that concrete concepts tend to be related to concrete concepts and abstract concepts tend to be related to abstract ones.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in subjects as varied as finance and medicine have used extractive summation, sentiment classification, and corpus-based stemming techniques, which are taken from this field of study (Arroyo-Fernández, Curiel, & Méndez-Cruz 2019); (Singh & Gupta, 2019); (Xu, Huang, Zhang, & Wang, (2019); (Xing, Cambria, & Zhang, (2019). Kwong (2008) examined the chronological evidence for internal lexicons and suggested that concrete senses are more readily activated than abstract ones and that broad associations are more easily triggered than narrow paradigmatic ones. Ion and Tufis (2009) describe two different WSD systems, one of which is applicable to parallel corpora and the other of which is less knowledge rich.…”
Section: Examples Of How To Pick a Good American President From 2016 ...mentioning
confidence: 99%